Rapid authentication of agarwood by using liquid extraction surface analysis mass spectrometry (LESA‐MS). Issue 6 (27th April 2020) - Xie, Yanqiao; Li, Linnan; Chen, Yilin; Yang, Yuangui; Xu, Hong; Wang, Zhengtao; Yang, Li
Abstract: Introduction: Agarwood is a highly valuable fragrant resinous wood which is widely used as traditional Chinese medicines, perfumes, incense and decorations. Due to its high economic value and excessive demand, this leads to a rising price and proliferation of fake commodities. Thus, strict authenticity identification and quality evaluation of agarwood are of great significance. Objective: To establish a simple, rapid and non‐destructive technique for identifying the authenticity of agarwood. Methods: Liquid extraction surface analysis mass spectrometry (LESA‐MS) was firstly proposed to identify the authenticity of 62 agarwood samples without sample preparation. In addition, multivariate statistical models and thin‐layer chromatography (TLC) method were used to analyse and verify the results of LESA‐MS. Results: Representative compounds of agarwood were detected by LESA‐MS. A characteristic 2‐(2‐phenylethyl)chromone compound ( m/z 319.1) was treated as a key chemical marker to identify agarwood and its counterfeits rapidly. Several other chromones ions were identified and used as additional evidence for authentic samples. A total of 62 samples were visually discriminated as two groups by principal component analysis (PCA) and orthogonal projection to latent structures discriminant analysis (OPLS‐DA), and the specific characteristic marker was highlighted. Moreover, the qualitative results of the conventional TLC method were in agreement with the LESA‐MS approach. Conclusion: The proposed LESA‐MS method was successfully applied in the direct qualitative analysis of agarwood from different sources. This study indicated great feasibility and practicality of LESA‐MS in the rapid identification of agarwood, and provided a non‐destructive and meaningful preliminary screening tool for the agarwood industry. Abstract : Agarwood is a highly valuable fragrant resinous wood and has been listed as endangered species in recent years. A new LESA‐MS method was established to rapidly identify authenticity of agarwood without sample preparation, some 2‐(2‐phenylethyl)chromone derivatives were detected and the characteristic 5, 6, 7, 8‐tetrahydro‐2‐(2‐phenylethyl)chromone ( m/z 319.1) was the most important compound to differentiate authentic agarwood from counterfeits. The developed LESA‐MS approach was demonstrated to be a simple, automated and non‐destructive technique for direct qualitative determination of agarwood.